Antibodies to shiga holotoxin and to two synthetic peptides of the B subunit in sera of patients with Shigella dysenteriae 1 dysentery. - Levine, M M (1992)
Acute- and convalescent-phase sera from 18 Thai patients and convalescent-phase sera from two Israeli patients and one Bangladeshi patient with Shigella dysenteriae 1 (Shiga) dysentery were tested by enzyme-linked immunosorbent assay to detect antibodies that bind S. dysenteriae lipopolysaccharide (LPS), Shiga holotoxin, or two synthetic peptides representing epitopes from the B subunit of Shiga toxin. Paired sera from 24 Maryland adults with Shigella flexneri 2a or Shigella sonnei diarrhea served as negative controls. Of the 16 paired Thai serum samples tested for immunoglobulin G LPS antibody, 10 had greater than or equal to 4-fold rises (the two subjects with the highest convalescent-phase titers exhibited toxin-neutralizing activity); acute-phase specimens from four of the remaining six individuals already had elevated Shiga LPS titers in their acute specimens ranging from 1:800 to 1:12,800. Similarly, convalescent-phase sera from the two Israeli patients and the Bangladeshi patient revealed LPS titers of 1:800 to 1:3,200. In contrast, none of the Maryland volunteers with S. flexneri or S. sonnei diarrhea manifested rises in Shiga anti-LPS (P less than 0.00001 versus 10 of 16 Thai patients). Only 4 of the 18 Thai patients had significant rise in antibody to purified Shiga toxin, while one of the two Israeli patients and the one Bangladeshi patient had elevated convalescent-phase titers. None of the sera that reacted with Shiga holotoxin had antibody that bound to the peptides. This report, which describes a search for serum antibodies that bind Shiga toxin in patients with Shiga dysentery, demonstrates such antibodies in only a minority of patients with bacteriologically confirmed disease. During Shiga dysentery, Shiga toxin may be elaborated in such small quantities in vivo that it fails to elicit an immune response in most patients even though it may exert biological effects. In this behavior Shiga toxin resembles tetanus toxin, another potent exotoxin that fails to elicit antitoxic responses in people who recover from clinical tetanus.